Unveiling the Motivation of Fraudulent Financial Statement in ENVY: Fraud Triangle Theory - Felicia Nathania (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to unravel the motivations behind the production of fraudulent financial statements by PT. Envy Technologies Indonesia Tbk. It employs a case study approach and the fraud triangle theory to shed light on this critical issue. This research is of paramount importance because fraudulent financial statements can have severe repercussions, adversely affecting shareholders and the broader capital markets. The primary findings of this investigation indicate that three key factors played a significant role in encouraging fraud within PT. Envy Technologies Indonesia Tbk. These factors are pressure, opportunity, and rationalization. The impetus for such fraudulent actions is traced back to the pressure exerted on maintaining high stock prices. The opportunities for manipulation arise from a deficiency in internal oversight mechanisms, enabling misconduct. Furthermore, rationalizations are formulated to justify the diversion of IPO funds in a manner that aligns with the information disclosed in the prospectus. This research offers a nuanced understanding of the factors that drive financial statement fraud in Indonesian public companies. It highlights that fraudulent activities are often the result of a combination of pressures, opportunities, and rationalizations. Recognizing these factors can be instrumental in implementing preventive measures to mitigate the occurrence of such fraud in the future.